1995
DOI: 10.1111/j.1476-5381.1995.tb13221.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of VEGF‐induced angiogenesis by the protein tyrosine kinase inhibitor, lavendustin A

Abstract: 3 Daily local administration of 250 ng VEGF165 accelerated the rate of "33Xe clearance from the sponges and induced an intense neovascularisation. This VEGF165-induced angiogenesis was inhibited by daily co-administration of the selective PTK inhibitor, lavendustin A (10 jig), but not its negative control, lavendustin B (10 jig). Blood flow measurements and morphometric analysis of 8-day-old sponges showed that lavendustin A reduced the "33Xe clearance of VEGF165-treated sponges from 32.9 ± 1.5% to 20.9 ± 1.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 34 publications
(30 reference statements)
1
25
0
2
Order By: Relevance
“…In our experiments, the effect of acetylcholine on Ltype currents could be reduced by the tyrosine kinase inhibitor genistein (Akiyama et al, 1987) and by lavendustin A (Hu and Fan, 1995 ;Onoda et al, 1989). Genistein and lavendustin A are structurally different substances and both lead to an inhibition of L-type current.…”
Section: Discussionsupporting
confidence: 47%
“…In our experiments, the effect of acetylcholine on Ltype currents could be reduced by the tyrosine kinase inhibitor genistein (Akiyama et al, 1987) and by lavendustin A (Hu and Fan, 1995 ;Onoda et al, 1989). Genistein and lavendustin A are structurally different substances and both lead to an inhibition of L-type current.…”
Section: Discussionsupporting
confidence: 47%
“…VEGF stimulates endothelial cells via tyrosine kinase receptors. VEGF-induced angiogenesis can be inhibited by reducing the protein tyrosine kinase activity [12].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Interestingly, it has been observed that VEGF and basic FGF (bFGF, or FGF-2) induce a synergistic angiogenic response, both in vitro 15,16 and in vivo. 17,18 A number of endogenous negative regulators have been described, including inhibitors of extracellular proteinases, thrombospondins 1 and 2, and bioactive fragments of the ECM and other molecules (see below). 1,19 -21 The notion of the "balance" applied to positive and negative regulators of angiogenesis can also be applied to extracellular proteolysis.…”
mentioning
confidence: 99%